2017
DOI: 10.12998/wjcc.v5.i9.360
|View full text |Cite
|
Sign up to set email alerts
|

Conservative approach to the acute management of a large mesenteric cyst

Abstract: Mesenteric cysts are rare, benign gastrointestinal cystic lesions, which are often non-troublesome and present as an incidental radiological finding. However, surgery is often performed in the acute setting to remove lesions that are symptomatic. This report highlights the case of a large, symptomatic mesenteric cyst managed successfully with initial conservative measures followed by planned elective surgery. A 44-year-old female presented with a four-day history of generalised abdominal pain associated with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 5 publications
0
25
0
1
Order By: Relevance
“…They are often asymptomatic and found incidentally when patients are undergoing investigations or treatment of another condition [4]. Clinical presentation includes nonspecific abdominal pain, abdominal distention, change in bowel habit, nausea, vomiting and an abdominal mass [5]. Rarely, they may present as an acute abdomen as a result of a complication such as intestinal obstruction, ischaemic bowel, volvulus and peritonitis or haemorrhagic shock secondary to rupture or bleeding into the cyst.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are often asymptomatic and found incidentally when patients are undergoing investigations or treatment of another condition [4]. Clinical presentation includes nonspecific abdominal pain, abdominal distention, change in bowel habit, nausea, vomiting and an abdominal mass [5]. Rarely, they may present as an acute abdomen as a result of a complication such as intestinal obstruction, ischaemic bowel, volvulus and peritonitis or haemorrhagic shock secondary to rupture or bleeding into the cyst.…”
Section: Discussionmentioning
confidence: 99%
“…Mesenteric cysts are mostly located in the ileum (60 %), ascending colon (24 %), retroperitoneum (14.5 %) and the omentum [4]. Clinical presentation is variable: often they are asymptomatic and found incidentally when patients are receiving work up for other conditions [5]. When patients are symptomatic, the most common presenting complaints are: pain (82 %), nausea and vomiting (45 %), constipation (27 %), and diarrhoea (6 %).…”
Section: Introductionmentioning
confidence: 99%
“…However, Leung et al have demonstrated that, in acute settings, conservative management followed by elective surgery is also a safe approach. 1 In our case, the patient's main concern of abdominal pain was managed conservatively with analgesics and broad-spectrum antibiotics, and laparotomy was performed 1 week later.…”
Section: F I G U R E 4 Abdominal Cavity After Complete Excision Of Thmentioning
confidence: 84%
“…Mesenteric cysts are uncommon benign intra-abdominal tumors that occur across the life course, with a reported incidence of 1/100 000 in adults and 1/20 000 in children and a female-to-male ratio of 2:1. 1 Lesions are typically located in the small bowel mesentery (66%) or large bowel mesentery (33%), 2 with occasional extension to the retroperitoneum. 3 Depending on their size and location, these cysts are often asymptomatic and are thus discovered incidentally during routine imaging; symptomatic cases may present with acute or chronic vague abdominal pain (55%-81%), a palpable mass (44%-61%), abdominal distension (17%-61%), nausea and vomiting (45%), constipation (27%), or diarrhea (6%).…”
Section: Introductionmentioning
confidence: 99%
“…Omental and mesenteric cysts are uncommon benign tumors usually occurring in children with an incidence of 1/20000 at infancy and 1/100000 to 1/250000 of hospital admissions in adults [1]. Sixty-five percent of cases are present at birth, and the female-to-male ratio is 2 : 1 [2]. In adults, they are rare and found in the age group between 40 and 70 years [3].…”
Section: Discussionmentioning
confidence: 99%